MONITORING OF ELECTRICAL SYSTEM USING INTERNET OF THINGS WITH SMART CURRENT ELECTRIC SENSORS - Muhammad Hafizd Ibnu Hajar; Akhmad Wahyu Dani; Satriyo Miharno (Universitas Mercu Buana, 2018)
Electricity is one of the most important human needs. In the presence of electricity it can facilitate human work. But it should be noted that too large and uncontrolled electricity use will be wasteful and get high costs. The problem is that electricity is not monitored accurately, easily and efficiently. This study aims to design an electric current monitoring device with an IoT system. IoT is a concept with the ability to transfer data by network, no need humans to humans or humans to PCs. In this concept, the SCT 013-000 electric current sensor is connected to the load, it will be show electric current value in the LCD, if the electric current which is determined exceeds the capacity, Wemos D1 including Wifi ESP 8266 will be sending a notification to the telegram. The system has been implemented with ironing load for 3.29%, the dispenser load is 0.20% and Magicom's get load for 1.07%. The delay time also has been implemented in the relay for 1.50 second when relay is on and 0.78 second when relay is off. When the notification send to the telegram also have a delay for 6.2 second. So, monitoring of electrical system using internet of things with smart current electric sensors has been done.